2016 IEEE International Instrumentation and Measurement Technology Conference Proceedings 2016
DOI: 10.1109/i2mtc.2016.7520481
|View full text |Cite
|
Sign up to set email alerts
|

On-line continuous measurement of the operating deflection shape of power transmission belts through electrostatic sensing

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…It is also noticeable that the signals share almost the same relative magnitudes of the spectral peaks. In comparison with the velocity response measured using electrostatic sensors with transresistance amplifiers [15], there are fewer spectral peaks at higher frequencies and the fundamental vibration mode has the largest magnitude. Note that the small spectral peaks at 50 Hz in Fig.…”
Section: Ods Measurement Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…It is also noticeable that the signals share almost the same relative magnitudes of the spectral peaks. In comparison with the velocity response measured using electrostatic sensors with transresistance amplifiers [15], there are fewer spectral peaks at higher frequencies and the fundamental vibration mode has the largest magnitude. Note that the small spectral peaks at 50 Hz in Fig.…”
Section: Ods Measurement Resultsmentioning
confidence: 91%
“…In previous studies [12][13][14][15], it was found that a dielectric belt running on earthed metal rollers carries electrostatic charge due to contact and frictional electrification. Information about the motion of the belt can be derived using electrostatic sensors placed adjacent to the belt.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations